Detection of heavy metals in palm oil at different stages of processing / Raihana Hani Zawawi and Suleha Abdul Aziz - Zawawi, Raihana Hani; Abdul Aziz, Suleha (2012)
Edible oils, in this case palm oil, were extracted and processed world-wide and important as domestic and international commodities. The determination of heavy metals in palm oil has gained more importance nowadays because they contain natural antioxidants and essential elements and also these oils were used in many aspects of food production, such as baking and frying and for the manufacturing of margarine, snack foods and other oil products. Samples collected from different stages of milling process were analyzed using Inductively Coupled Plasma - Optical Emission Spectroscopy (ICP-OES) to determine the presence and types of heavy metals found in the oil. Determination of heavy metals in palm oil samples using ICP-OES has been proved to be reliable, fast and precise method. The amounts of heavy metals detected were under maximum level of CODEX Standard but still can be improved so that the quality of our palm oil products can be further improved.